Antioxidant and toxicity activities of Artocarpus lakoocha Roxb. heartwood extract - Supawatchara Singhatong (2018)
The antioxidant activity of Artocarpus lakoocha heartwood extract was investigated from ethanol extraction by 2,2'-azino-bis(3-ethylbenzthiazoline-6-sulphonic acid) (ABTS) decolorization, 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical and H 2O 2 scavenging assay. Polyphenolic; total phenolic, flavonoids and tannins were measured. Anti-oxidative stress was studied in AAPH-oxidized blood and glutathione (GSH), and malondialdehyde (MDA) was evaluated. Results showed that antioxidant activities were 128.30 ± 0.13, 55.86 ± 0.01, and 463.49 ± 0.01 μmol Trolox/g extracted from ABTS, DPPH, and H 2O 2 scavenging methods. One gram of extract contained total phenol (325.63 ± 2.99 mg GE), flavonoids (521.98 ± 0.01 mg QE) and tannins (124.03 ± 0.46 g TE), including rutin and resocinol. In the blood system, a low concentration of extract inhibited MDA progression and improved GSH, which was in contrast to a high concentration with its toxicity effect.